Assessment of recreational potential of Sevastopol bays using bioindication methods - Т. В. Sigacheva; I. I. Chesnokova; О. L. Gostyukhina; S. V. Kholodkevich; Т. V. Kuznetsova; Т. I. Andreenko; N. P. Kovrigina; T. V. Gavruseva; M. P. Kirin; A. S. Kurakin (Юг России: экология, развитие)
Aim. Study of a group of biochemical parameters of the hepatopancreas and gills of the Black Sea mussel Mytilus galloprovincialis Lam. and the functional indicator of cardiac system adaptivity of mussels from Sevastopol bays with different levels of recreational and anthropogenic impact.Methods. Mussels were collected from four Sevastopol water areas (Kruglaya Bay, Kazachya Bay, Matyushenko Bay and Cape Khrustalnii) in autumn 2018. The bioindication methods used were based on application of functional (cardiac system adaptability) and biochemical indicators (antioxidant enzymes activity [AEA], aminotransferases, the alkaline phosphatase [AP], and products of the lipid peroxidation [LPO] and protein oxidation [PO]) of mussel tissues. The hydrochemical parameters of the investigated areas were determined.Results. The anthropogenic impact on a complex of biochemical indicators of mussels at the sampling sites was shown. At the same time, low values of mussel heart rate (HR) recovery time (Trec) (less than 60 min.) in all sampling sites demonstrated the efficiency of biochemical changes in mussels and the possible use of all tested bays as recreational areas.Conclusion. Results of the present research allow the characterization of the ecological status of these Sevastopol sea water areas and to make recommendations about their rational use. Matyushenko and Kazachya Bays are most suitable for beach recreation and recreational fishery. Kazachya Bay also has favourable conditions for the development of water sports. Kruglaya Bay and Cape Khrustalnii are less ecologically safe and require a series of actions to improve water quality.